The Impact of Mass Media on International Politics in Arab Countries (The International Journal for Scientific Research, 2023)
The study aims to study the influence of the media on international politics, and to support the axes of the thesis with case studies from various platforms and media outlets that lived through the phases of the democratic Arab Spring series in all the Arab countries that the thesis will address to talk about. The studies included in the content of the thesis reveal the available conceptual and theoretical links. Between the information and communication revolution on the one hand, and the democratic transition on the other. From these basic concepts and relationships, there are many objectives that are based on the influence exerted by the most prominent manifestations of the communications and information revolution, such as satellite television channels and the Internet, in their relationship to the process of forming public opinion, institutions, bodies and parties in the Arab region. The study also aims to democratize and build systems and institutions in the region. Al-Arabiya operates according to a forward-looking vision for political and social relations.
Keywords: Information revolution; communication technology; societal democracy; democratic transformation in the Arab countries